DESAIN DIDAKTIS KONSEP SEGIEMPAT BERDASARKAN LEARNING OBSTACLE PADA PEMBELAJARAN MATEMATIKA KELAS VII - Winda Wulandari; Rianti Cahyani (UJMES (Uninus Journal of Mathematics Education and Science), 2020)
The background of this research on the rectangular study is learning obstacle (LO) experienced by learners. Instructional design based on the LO experienced learners is one alternative to reduce of learning obstacle. This research aims (1) identified LO on rectangular study, (2) develop of the didactical design based on LO and relevant learning theories, (3) describe the didactical design after implementation. This research used didactical design research and qualitative approach. Data collection techniques used triangulation techniques. Research conducted at SMP Al-Qona’ah Baleendah with the subjects 38 learners class of VIII-B and 36 learners class of VII-A. The first step in the research is the analysis of the situation by conducting a test didactical diagnostic tests and interview semi-structure to identify learning obstacle experienced by learners. The second step devised a didactical design based LO and reinforced by relevant learning theories. The result of the design implementation are analyzed based on the metapedadidaktik analysis and retrosfektif analysis. The results concluded that: (1) There are four types of rectangular LO, (2) the didactical design is based on the identified LO of the learners, (3) the result of the implementation showed that didactical design can reduce LO experienced learners.